(untitled) (Global Journal of Human-Social Science, 2019)
Became a fluent reader is one of the aims of the reading learning process. In previous researches, the relationship between oral and silent reading fluency and text reading comprehension has been investigated with different results. According to the variety of information about the topic, the purpose of this work is to compare oral and silent reading fluency to establish possible differences between reading modalities and the implications for reading comprehension. A sample of 171 children from 3rd, 5th, and 7th grade answered three tasks: a standardized word and non-word reading task, an oral reading comprehension task, and a silent reading comprehension task, both designed ad hoc. In order to compare the three groups of students, time measures and accuracy were calculated for word and no-word reading task, and time and comprehension measures were considered for oral and silent reading comprehension tasks.